Comparison of 18F-DCFPyL and 68Ga-PSMA-11 for 177Lu-PSMA-617 therapy patient selection - Yadav, Surekha; Kim, Sarasa T.; Tuchayi, Abuzar Moradi; Jiang, Fei; Morley, Amanda; Saelee, Rachelle; Wang, Yingbing; Juarez, Roxanna; Lawnh-Heath, Courtney; Koshkin, Vadim S.; Hope, Thomas A. (Frontiers in Oncology, 2024)
Ga-PSMA-11 is recommended for the selection of patients for treatment in the package insert for 177 Lu-PSMA-617. We aimed to compare imaging properties and post-treatment outcomes from radioligand therapy (RLT) of patients selected with 68 Ga-PSMA-11 and 18 F-DCFPyL.We retrospectively evaluated 80 patients undergoing PSMA RLT, who had pretreatment imaging using either 68 Ga-PSMA-11 or 18 F-DCFPyL. For both groups, we compared the biodistribution and lesion uptake, as well as the PSA response to treatment.Both agents had comparable biodistribution. Patients initially imaged with 18 F-DCFPyL had a higher PSA response (66% vs 42%) and more patients had a PSA50 response (72% vs 43%) compared to patients imaged with 68 Ga-PSMA-11.CONCLUSION: 18 F-DCFPyL and 68 Ga-PSMA-11 had comparable biodistribution and lesion uptake. Patients imaged with 18 F-DCFPyL demonstrated clinical benefit to PSMA RLT comparable to those imaged with 68 Ga-PSMA-11, and either agent can be used for screening patients.